INSTITUTIONAL BRANDING STRATEGIES THROUGH INTERNAL ENGLISH CAMP AT ISLAMIC BOARDING SCHOOL - Saryati Purwanigara (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Speaking proficiency in English is an essential competence in the era of globalization, especially for students in educational environments such as Islamic boarding schools. This study aims to evaluate the effectiveness of the Internal English Camp Program in enhancing students’ English-speaking skills at SMPIT Thariq bin Ziyyad Boarding School, Bekasi. A descriptive qualitative approach was employed, utilizing observation, interviews, and questionnaires involving 30 student participants of the program. The results indicate that the program significantly increased students’ motivation, confidence, and frequency of English usage in daily activities. Communicative and interactive learning methods, supported by experienced instructors from Kampung Inggris Pare, established a conducive and enjoyable learning environment. The majority of respondents rated the program very positively and reported noticeable improvements in their speaking skills and motivation to learn. These findings underscore the importance of language-rich environments and programs such as the Internal English Camp as effective strategies for fostering English-speaking proficiency in Islamic boarding schools and other residential educational settings. ABSTRAK Kemampuan berbicara dalam bahasa Inggris merupakan kompetensi esensial di era globalisasi dan sangat diperlukan bagi siswa di lingkungan pendidikan, termasuk pesantren. Penelitian ini bertujuan untuk mengevaluasi efektivitas Program Internal English Camp dalam meningkatkan keterampilan berbicara Bahasa Inggris siswa di SMPIT Thariq bin Ziyyad Boarding School, Bekasi. Studi ini menggunakan pendekatan kualitatif deskriptif dengan teknik observasi, wawancara, dan kuesioner yang melibatkan 30 siswa peserta program. Hasil penelitian menunjukkan bahwa program ini secara signifikan meningkatkan motivasi, kepercayaan diri, dan frekuensi penggunaan bahasa Inggris dalam kehidupan sehari-hari siswa. Metode pembelajaran yang komunikatif, interaktif, serta didukung oleh instruktur berpengalaman dari Kampung Inggris Pare, menciptakan lingkungan belajar yang kondusif dan menyenangkan. Sebagian besar responden memberikan penilaian sangat baik terhadap program, serta melaporkan adanya peningkatan keterampilan berbicara dan motivasi belajar. Temuan ini mempertegas pentingnya penerapan program berbasis lingkungan bahasa yang mendukung, seperti Internal English Camp, sebagai strategi efektif untuk mengembangkan keterampilan berbicara bahasa Inggris di boarding dan sekolah berasrama lainnya.